Semantic properties of effective constructions in English and Uzbek languages - Davlatova , Muhayyo (The Lingua Spectrum, 2025)
This article is devoted to the study of the grammatical research center of each language, phenomena are expressed as linguistic units, and interconnected participation ensures the establishment of units. These types of grammatical analysis are known in the history of linguistics under many terms: grammatical relations, syntactic functions, sub categorization of frames, argument-containing constructions, argument dependence, etc. One of the main problems associated with each branch of grammar is the choice of the correct relationship of similarity and difference in this language and in the context of other languages.